Strategi Dakwah Masjid Baiturrahim Danukusuman dalam Menghadapi Krisis Moral Generasi Muda: Baiturrahim Danukusuman Mosque's Preaching Strategy in Facing the Moral Crisis of the Young Generation - Muhammad Hafizh Nafi' Maftazany; Muhammad Danar Prakoso; Rakha Hadimulya; Dwezille Satritama Ghazali; Muhammad Ilham Perdana; Kholifatul Iman; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This community service study examines the moral crisis affecting youth around Baiturrahim Mosque in Danukusuman and develops a participatory da’wah strategy to address it. The approach comprised participatory observation, collaborative planning with stakeholders, and implementation of a Qur’anic Education Program integrating tazkiyah al-nafs, interactive pedagogy, historical storytelling, and multicultural modules. Outcomes reveal increased enthusiasm and discipline among participants, enhanced comprehension of core Islamic values, and strengthened emotional bonds between youth and instructors. The discussion highlights the efficacy of an integrative theoretical framework—combining mental well-being, experiential learning, and multicultural education—as a sustainable contextual da’wah model. These findings recommend replicating this strategy in other religious institutions to rejuvenate youth character and spirituality in the modern era.